A QUANTITATIVE STUDY ON ANALYSING THE DETERMINANTS OF OUT-OF-SCHOOL IN URBAN INDIA - Maggo, Vidhi; Gupt, Yamini (International Journal of Research -GRANTHAALAYAH, 2023)
This study attempts in investigating the reasons for out-of-school in urban India and analyse the factors that are responsible for children aged 5-18 years to discontinue education. For this, the study employs secondary data by pooling the 71st and 75th NSSO rounds (Education survey). The study finds that majority of girl students drop out to take care of household duties while boys dropout to take jobs to supplement household earnings. Other reasons include school being far off, lack of infrastructural amenities and disinterest in education. By using Logit regression this study presents evidence on likelihood of being out-of-school affected by social background and household characteristics. Muslim children and those belonging to lower caste face higher chance of being out of school. Children belonging to poor families drop out sooner and girls face a larger exclusion from continuing education in comparison to boys. Households that have more members also witness more dropouts while educated head of the household creates positive spill over in reducing dropout by motivating younger generation to continue education. Against this backdrop, the study suggests target specific programmes have to be laid so that awareness about the significance of continuing education can reach the disadvantaged and financially deprived sections of society. To address rising dropout rate, a proper strategy has to be undertaken by the government to promote human capital accumulation through encouraging female education.